Heme catabolism in the causative agent of anthrax. Issue 2 (27th May 2019) - Clark, Justin; Terwilliger, Austen; Nguyen, Chinh; Green, Sabrina; Nobles, Chris; Maresso, Anthony
Summary: A challenge common to all bacterial pathogens is to acquire nutrients from hostile host environments. Iron is an important cofactor required for essential cellular processes such as DNA repair, energy production and redox balance. Within a mammalian host, most iron is sequestered within heme, which in turn is predominantly bound by hemoglobin. While little is understood about the mechanisms by which bacterial hemophores attain heme from host‐hemoglobin, even less is known about intracellular heme processing. Bacillus anthracis, the causative agent of anthrax, displays a remarkable ability to grow in mammalian hosts. Hypothesizing this pathogen harbors robust ways to catabolize heme, we characterize two new intracellular heme‐binding proteins that are distinct from the previously described IsdG heme monooxygenase. The first of these, HmoA, binds and degrades heme, is necessary for heme detoxification and facilitates growth on heme iron sources. The second protein, HmoB, binds and degrades heme too, but is not necessary for heme utilization or virulence. The loss of both HmoA and IsdG renders B. anthracis incapable of causing anthrax disease. The additional loss of HmoB in this background increases clearance of bacilli in lungs, which is consistent with this protein being important for survival in alveolar macrophages. Abstract : Heme is a major source of essential nutrient iron for bacterial pathogens in a mammalian host. Here we describe two new heme‐degrading enzymes, HmoA and HmoB, in the causative agent of anthrax and demonstrate that HmoA allows for detoxification and utilization of heme iron. We also show that HmoA is functionally redundant with a previously described heme‐degrading enzyme, IsdG and together they are essential for the development of inhalational anthrax in an animal model.